2015
DOI: 10.1002/jor.23049
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensionality of gleno‐humeral deformities in obstetrical brachial plexus palsy

Abstract: The primary objective of this study was to test the hypothesis that gleno-humeral deformity in children and adolescent with obstetrical brachial plexus palsy is three-dimensional (3D). The study also compared the metrological properties of typical two-dimensional gleno-humeral measures to the newly developed 3D measures. Thirteen individuals (age = 11.8 ± 3.3 years) with obstetrical brachial plexus palsy participated in this IRB-approved study. 3D axial magnetic resonance images were acquired for both shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
0
17
2
Order By: Relevance
“…Muscles with a moment arm greater than 6 mm in a specific torque direction were considered as contributors to that torque. This qualitative cut-off was slightly higher than our previous study 21 due to the potential alteration in moment arms secondary to the bone deformities and humeral head migration in OBPP 22 . This resulted in the entire deltoid being considered an abductor, its anterior segment a flexor, and its posterior segment an extensor 26 .…”
Section: Methodscontrasting
confidence: 62%
See 2 more Smart Citations
“…Muscles with a moment arm greater than 6 mm in a specific torque direction were considered as contributors to that torque. This qualitative cut-off was slightly higher than our previous study 21 due to the potential alteration in moment arms secondary to the bone deformities and humeral head migration in OBPP 22 . This resulted in the entire deltoid being considered an abductor, its anterior segment a flexor, and its posterior segment an extensor 26 .…”
Section: Methodscontrasting
confidence: 62%
“…Data from an ongoing IRB (National Institute of Child Health and Human Development, intramural, MD, USA) approved study 4,22,21,23 formed the basis of this case-controlled study. Sixteen children/adolescents with unilateral OBPP were recruited as a sample of convenience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though glenoid version angle is the most common clinical measure of glenoid deformity in NBPI, glenoid deformity may not be limited to the axial plane. Two recent studies that evaluated the three‐dimensional morphology of the glenoid found that the glenoid on the affected side was significantly more retroverted and declined in children with NBPI . Another study found that glenoid retroversion deformity severity was negatively correlated with glenoid declination deformity severity .…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of incomplete neurological recovery range widely, but were reported to be as high as 27% in one prospective large‐scale study . Infants without full neurological recovery predominantly display glenoid retroversion, which may also be accompanied by posterior humeral head subluxation, malformation of the humeral head and glenoid, and glenoid declination . Rotator cuff muscular imbalance and internal rotation contracture is also attributed to NBPI, with associated subscapularis shortening and stiffening, and weakening or paralysis of the infraspinatus and supraspinatus .…”
mentioning
confidence: 99%